Una poética de la sacralidad: La escritura cósmica en “Amaru” de Edgardo Rivera Martínez - Mudarra Montoya, Américo (2021)
The article focuses on showing the value of this story, “Amaru”, inside Edgardo Rivera Martinez’s narrative. We believe that it deals with a cardinal narration since it constitutes a poetics; this text generates the conception of a cosmic writing, linked to the nature and to the time, that tries to set the ineffable thing.